The Influence Of Organizational Climate, Training, And Compensation On Employee Job Satisfaction In The Dgt Regional Office, North Sumatra - Andrianta Bangun, Nugraha; Wahyuni, Rahayu; Dawi, Umar; Desember, Anita; Lubis, Hasrita; Riana, Zenni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This exploration expects to determine the impact of an authoritative environment, prepare and pay somewhat, and at the same time, fulfill representative work at the DJP North Sumatra I Provincial Office. The examination was led at the North Sumatra I DJP Provincial Office Jalan Sukamulia No. 17A Medan, with a population of 145 individuals and an exploration test of 59 individuals. Information assortment was completed through meetings, polls and documentation. The information examination procedure utilized was a different relapse investigation involving the IMB Measurements for Item and Administration Arrangement (SPSS) PC program adaptation 24. In light of the aftereffects of the examination, it was found that the authoritative environment affected work fulfillment for representatives of the North Sumatra Local Office of DJP I. This was upheld by the consequences of the examination, t count < t-table (0.955 < 2.004) at n = 59 at the 95% importance level. Preparing affects the work fulfillment of representatives of the North Sumatra Provincial Directorate General Office I; this is upheld by the examination of t count > t-table (2.662 > 2.004) at n = 59 at an importance level of 95%. Pay significantly affects the work fulfillment of representatives at the North Sumatra Local Directorate General Office I; this is upheld by the examination of t count > t-table (3.655 > 2.004) at n = 59 with an importance level of 95%. F-count esteem > F table (18.016 > 2.78) This expresses that together (differently), there is a positive and huge impact of the hierarchical environment, preparing and pay on the work fulfillment of representatives of the North Sumatra Provincial Office of DJP.